Influência de fatores nutricionais sobre o crescimento de Streptococcus zooepidemicus: um estudo experimental - Klein, Camila (My University, 2025)
Hyaluronic acid is an organic acid widely used in the cosmetic and pharmaceutical industries. This compound can be obtained by culturing Streptococcus zooepidemicus. This article evaluated the growth of S. zooepidemicus in different media formulations, exploring variations in glucose concentration (5, 10, 20, and 30 g L) and the effects of media supplementation with nutrient salt solution. Cell growth, glucose consumption, and pH were analyzed as a function of cultivation time. The higher results of growth were attained using N20 synthetic medium (supplemented) and S20 medium (unsupplemented), of 1.43 and 1.35 g L, respectively, both containing 20 g L of glucose, in 48 hours of cultivation. Considering N30 synthetic medium (supplemented), cell biomass of 1.26 g L was also quantified at 48 hours. The cultivations carried out with lower glucose concentration, S5 and S10, showed cell growth of 0.98 g L and 1.0 g L, respectively, in 48 hours of process. These results suggest that intermediate glucose concentrations (20 g L) and supplementation with mineral salts favored bacterial growth in synthetic medium. The acidification observed in all of conditions indicates a possible metabolic shift toward organic acids production, indicating the importance of further analysis. [resumo fornecido pelo autor]
O ácido hialurônico é um ácido orgânico amplamente utilizado nas indústrias cosmética e farmacêutica. Esse composto pode ser obtido através do cultivo de Streptococcus zooepidemicus. Este artigo avaliou o crescimento de S. zooepidemicus em diferentes formulações de meios, explorando variações na concentração de glicose (5, 10, 20 e 30 g L) e os efeitos da suplementação do meio com solução salina nutritiva. O crescimento celular, o consumo de glicose e o pH foram analisados em função do tempo de cultivo. Os resultados mais elevados de crescimento foram obtidos utilizando o meio sintético N20 (suplementado) e o meio S20 (não suplementado), de 1,43 e 1,35 g L, respectivamente, ambos contendo 20 g L de glicose, em 48 horas de cultivo. Considerando o meio sintético N30 (suplementado), a biomassa celular de 1,26 g L também foi quantificada em 48 horas. Os cultivos realizados com menor concentração de glicose, S5 e S10, apresentaram crescimento celular de 0,98 g L e 1,0 g L, respectivamente, em 48 horas de processo. Esses resultados sugerem que concentrações intermediárias de glicose (20 g L) e suplementação com sais minerais favoreceram o crescimento bacteriano em meio sintético. A acidificação observada em todas as condições indica uma possível mudança metabólica para a produção de ácidos orgânicos, indicando a importância de análises adicionais. [resumo fornecido pelo autor]
Keywords: Ácido hialurônico; Streptococcus equi; Microorganismos